2018
DOI: 10.1139/cjas-2017-0012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diets containing linseed oil or lard and supplemented with pumpkin seeds on oxidative status, blood serum metabolites, growth performance, and meat quality of naked neck chickens

Abstract: This study investigates the effect of two dietary fats, namely linseed oil (LO) and lard (LF), and supplementation with pumpkin seeds (PS) on the performance, oxidative status, and blood serum metabolites of broilers, along with the composition, oxidative stability, and fatty acid (FA) profile of broiler meat. Ninety-six 64-d-old naked neck chickens were randomly distributed into four groups of 24 chickens each (8 chickens per cage, three cages per treatment) and fed a LO diet, a LO diet supplemented with 50 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 64 publications
2
3
0
Order By: Relevance
“…Similar research has shown that these essential fatty acids can lower bad cholesterol and prevent cardiovascular disease. Pumpkin seed has been reported to possess cholesterol lowering effect and these results are in agreement with the observations of previous researchers (Meineri et al, 2018;Fruhwirth and Hermetter, 2007). This is similar with the finding of Perez-Gutierrez (2016) who reported that Glycemia and cholesterol levels were significantly (p<0.05) lower in the serum of chicken fed pumpkin seed supplemented diets than in those fed diet without pumpkin seed supplementation.…”
Section: Discussionsupporting
confidence: 92%
“…Similar research has shown that these essential fatty acids can lower bad cholesterol and prevent cardiovascular disease. Pumpkin seed has been reported to possess cholesterol lowering effect and these results are in agreement with the observations of previous researchers (Meineri et al, 2018;Fruhwirth and Hermetter, 2007). This is similar with the finding of Perez-Gutierrez (2016) who reported that Glycemia and cholesterol levels were significantly (p<0.05) lower in the serum of chicken fed pumpkin seed supplemented diets than in those fed diet without pumpkin seed supplementation.…”
Section: Discussionsupporting
confidence: 92%
“…By contrast, the L diet positively affected the n‐3 PUFA, and indeed the n‐3 is significantly higher in the L diet than in the corresponding Ct groups (Figure 2). Both these results are commonly found in the literature (Hang et al, 2018; Head et al, 2019; Meineri et al, 2018). Head et al (2019) described the modulation of FA profile in a given tissue through the diet, and also provided insights into low effect of the diet on the gene expression.…”
Section: Discussionsupporting
confidence: 82%
“…The results of the studies indicate that a diet rich in components with high antioxidant potential contributes to the reduction of the risk of developing cardiovascular diseases, cancer (Aune et al, 2018) and Diabetes mellitus (Hamer & Chida, 2007). Antioxidant compounds (including bioactive compounds contained e.g., in pumpkin seeds) can also reduce blood glucose levels in animals with impaired carbohydrate metabolism (Meineri et al, 2018;Salvador et al, 2017). The consumption of antioxidants is associated with a reduction in the risk of neurodegenerative diseases, including Alzheimer's disease (Li et al, 2012).…”
Section: Introductionmentioning
confidence: 99%